Reinterpretation and Development of Effective Risk Management in Indonesian Peer-to-Peer Lending - Ramadhani, Rona Almas; Dewantara, Reka; Ruslijanto, Patricia Audrey (International Journal of Business, Law, and Education, 2026)
This study examines the reinterpretation and development of effective risk management in Indonesia’s peer-to-peer lending regulation under Financial Services Authority Regulation Number 40 of 2024, which replaces the previous 2022 regulatory framework. The study aims to address the persistent ambiguity in defining “effective risk management,” which may result in inconsistent implementation among platform providers. Using a normative juridical method and a comparative analysis of international regulatory frameworks, this study identifies key elements of risk management relevant to digital financial services. The findings indicate that, although the updated regulation emphasizes governance and risk control, it still lacks clear technical indicators and measurable operational standards, thereby limiting its implementation effectiveness. This study concludes that more detailed legal standards and operational guidelines are required to enhance legal certainty, strengthen consumer protection, and support financial system stability within the evolving fintech ecosystem.